Daya Tarik Gelombang Bono Sebagai Objek Wisata Unggulan di Kabupaten Pelalawan - Yuliarti, Rini; Syaputra, Doddy (Komunitas Manajemen Kompetitif, 2015)
Abstract: The Travel Attractions Bono was amazing and unmatched so as to attract tourists to come to the District Pelalawan. For world surfers (surfers) and tourists from outside, Waves Bono Kampar is an amazing discoveries reveal even the world selencar remarkable for